An integrated decision support system for BIM level 3 implementation - Abumoeilak, Lama; Beheiry, Salwa; Atabay, Serter (Frontiers in Built Environment, 2025)
The Architecture, Engineering, and Construction (AEC) sector accounts for 39% of greenhouse gas emissions, 40% of solid waste, and 12% of potablewater usage globally, underscoring the need for sustainable, efficient practices. Building Information Modeling (BIM) offers a digital framework to address these challenges through lifecycle management, collaboration, and efficiency gains. However, most organizations remain at BIM Level 2 maturity, which limits their potential for full integration. This study proposes a comprehensive Decision Support System (DSS) to facilitate the adoption of BIM Level 3, with an emphasis on collaboration, sustainability, and data interoperability. The DSS integrates Structural Equation Modeling (SEM), Analytical Hierarchy Process (AHP), and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to identify and prioritize key drivers—including political, economic, socio-cultural, technological, legal, and environmental factors. The framework is validated through case studies, demonstrating its ability to align organizational strategies with sustainable practices. Organization (A) highlighted several essential components, ensuring a comprehensive assessment of BIM level 3 implementation within the organization. On the other hand, organization (B) stressed the importance of comparing the predicted environmental performance outcomes generated by the DSS with actual performance data collected during the building’s occupancy phase to validate the system’s predictive capabilities. These findings offer a practical pathway for achieving BIM Level 3 maturity, enhancing efficiency, supporting digital transformation, and advancing sustainability in the AEC industry.